2020
DOI: 10.21203/rs.2.24605/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of delayed diagnosis and treatment of tuberculosis in high-burden countries: a mixed-methods systematic review and meta-analysis

Abstract: Background: Globally, 30 countries with the highest tuberculosis (TB) burden bears 87% of the world’s TB cases. Delayed diagnosis and treatment are detrimental to TB prognosis and sustain TB transmission in the community, making TB elimination a great challenge, especially in these countries. Our objective was to elucidate the determinants and duration of delayed diagnosis and treatment of pulmonary TB in high TB burden countries. Methods: We conducted a systematic review and meta-analysis of quantitative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 119 publications
(309 reference statements)
1
3
0
Order By: Relevance
“…The male participants sought treatment and diagnosis less because of alcohol consumption and overt ego, confining symptoms for a long period. This agrees with the study by Teo et al, who found that women are simultaneously committed to many tasks that keep them away from personal healthcare, while men are patriarchal and therefore downplay healthcare. Health awareness tailored toward the specific need of each gender should be carried out, with focus on vulnerable populations.…”
Section: Discussionsupporting
confidence: 93%
“…The male participants sought treatment and diagnosis less because of alcohol consumption and overt ego, confining symptoms for a long period. This agrees with the study by Teo et al, who found that women are simultaneously committed to many tasks that keep them away from personal healthcare, while men are patriarchal and therefore downplay healthcare. Health awareness tailored toward the specific need of each gender should be carried out, with focus on vulnerable populations.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the effect of stigma on delayed TB diagnosis [ 7 ], IDI participants also reported that encouragements from family members, friends, and notably TB survivors were instrumental in facilitating TB care-seeking. One apparent link to the current TB policy in Cambodia was the implementation of the community directly observed treatment, short-course (C-DOTS).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the specific determinants of delayed diagnosis can be used as a practical guide to enhance outreach programs, increase community engagement to reach missing cases, and to improve TB control strategies. Recent systematic reviews have reported empirical evidence associating socio-demographic, clinical, health system, and economic factors with delayed diagnosis and treatment of TB [8][9][10]. In Cambodia, Sundaram and colleagues have reported that strong preference for private healthcare services, lack of awareness of TB symptoms, and misbeliefs regarding TB (such as TB is a hereditary disease and the ability to recover without treatment) may delay seeking TB diagnosis [11].…”
Section: Introductionmentioning
confidence: 99%